Idiosyncrasies of Volcanic Sulfur Viscosity and the Triggering of Unheralded Volcanic Eruptions - Scolamacchia, Teresa; Cronin, Shane J. (Frontiers in Earth Science, 2016)
Unheralded “blue-sky” eruptions from dormant volcanoes cause serious fatalities, such as at Mt. Ontake (Japan) on 27 September 2014. Could these events result from magmatic gas being trapped within hydrothermal system aquifers by elemental sulfur (Se) clogging pores, due to sharp increases in its viscosity when heated above 159oC? This mechanism was thought to prime unheralded eruptions at Mt. Ruapehu in New Zealand. Impurities in sulfur (As, Te, Se) are known to modify S-viscosity and industry experiments showed that organic compounds, H2S, and halogens dramatically influence Se viscosity under typical hydrothermal heating/cooling rates and temperature thresholds. However, the effects of complex sulfur compositions are currently ignored at volcanoes, despite its near ubiquity in long-lived volcano-hydrothermal systems. Models of impure S behavior must be urgently formulated to detect pre-eruptive warning signs before the next “blue-sky” eruption